Electrically Enhanced Transition Metal Dichalcogenides as Charge Transport Layers in Metallophthalocyanine-Based Solar Cells - Manamela, Lebogang; Fru, Juvet N.; Kyesmen, Pannan I.; Diale, Mmantsae; Nombona, Nolwazi (Frontiers in Chemistry, 2020)
Transitional metal dichalcogenides (TMDs) such as molybdenum disulfide (MoS2) have found application in photovoltaic cells as a charge transporting layer due to their high carrier mobility, chemical stability and flexibility. In this research, a photovoltaic device was fabricated consisting of copper phthalocyanine (CuPc) as the active layer, exfoliated and Au-doped MoS2, which are n-type and p-type as electron and hole transport layers, respectively. XRD studies showed prominent peaks at (002) and other weak reflections at (100), (103), (006) and (105) planes corresponding to those of bulky MoS2. The only maintained reflection at (002) was weakened for the exfoliated MoS2 compared to the bulk, which confirmed that the material was highly exfoliated. Additional peaks at (111) and (200) planes were observed for the Au doped MoS2. The interlayer spacing (d002) was calculated to be 0.62 nm for the trigonal prismatic MoS2 with the space group P6m2. Raman spectroscopy showed that the E12g (393 cm-1) and A1g (409 cm-1) peaks for exfoliated MoS2 are closer to each other compared to their bulk counterparts (378 cm-1 and 408 cm-1, respectively) hence confirming exfoliation. Raman spectroscopy also confirmed doping of MoS2 by Au as the Au-S peak was observed at 320 cm-1. Exfoliation was further confirmed by SEM as when moving from bulky to exfoliated MoS2, a single nanosheet was observed. Doping was further proven by EDS, which detected Au in the sample suggesting the yield of a p-type Au-MoS2. The fabricated device had the architecture: Glass/FTO/Au-MoS2/CuPc/MoS2/Au. The incorporation of the p and n-type MoS2 resulted in a flexible solar cell with enhanced stability and enhanced charge carrier mobility compared to conventional solar cells. Upon illumination, the device was able to absorb photons to create electron-hole pairs and it was evident that semipermeable junctions were formed between Au-MoS2/CuPc and CuPc/MoS2 as holes and electrons were extracted and separated at respective junctions generating current from light. This study indicates that the exfoliated and Au-MoS2 could be employed as an electron transporting layer (ETL) and hole transporting layer (HTL) respectively in fabricating photovoltaic devices.